Potentials of Acremonium butyri fungus in pre-treatment and hydrolysis using Rice husk substrate for biofuel production: A short communication - Sanusi, A.; Sanusi, A.; Farouq, A. A.; Ibrahim, A. D.; Shamsudeen, M. M.; Usman, M. H.; Bello, A. Y (UMYU Journal of Microbiology Research)
There is increasing interest in the area of biofuel production due to fear of fossil fuel extinction as a result of over exploitation and crises. During biofuel production, substrate needs to undergo pre-treatment and hydrolysis where acids and alkali are mostly used. In this study, Acremonium butyri was used for both pre-treatment and hydrolysis. Structural compositions of the rice husk were determined. Extractives, hemicellulose and Lignin content was determined via extraction using Soxhlet extractor while cellulose was determined as the difference from the extractives, hemicelluloses and lignin. Acremonium butyri was isolated from dried roots of Piliostigma reticulatum (Kalgo) by keeping the roots in a clean plastic for a period of 7 days on moist environment after which fungal growth appeared. The growth was aseptically transferred on to prepared S.D.A plate and kept at room temperature. The fungal growth was identified as based on the physical and microscopic characteristics. About 50g of rice husk was mixed with 500 ml of distilled water in the ration of 1:10 to obtain homogenous slurry and then inoculated with 2ml of prepared Acremonium butyri solution and incubated at room temperature for up to